A Changing Hydrological Regime: Trends in Magnitude and Timing of Glacier Ice Melt and Glacier Runoff in a High Latitude Coastal Watershed. Issue 7 (21st July 2021) - Young, Joanna C.; Pettit, Erin; Arendt, Anthony; Hood, Eran; Liston, Glen E.; Beamer, Jordan
Abstract: With a unique biogeophysical signature relative to other freshwater sources, meltwater from glaciers plays a crucial role in the hydrological and ecological regime of high latitude coastal areas. Today, as glaciers worldwide exhibit persistent negative mass balance, glacier runoff is changing in both magnitude and timing, with potential downstream impacts on infrastructure, ecosystems, and ecosystem resources. However, runoff trends may be difficult to detect in coastal systems with large precipitation variability. Here, we use the coupled energy balance and water routing model SnowModel‐HydroFlow to examine changes in timing and magnitude of runoff from the western Juneau Icefield in Southeast Alaska between 1980 and 2016. We find that under sustained glacier mass loss (−0.57 ± 0.12 m w. e. a −1 ), several hydrological variables related to runoff show increasing trends. This includes annual and spring glacier ice melt volumes (+10% and +16% decade −1 ) which, because of higher proportions of precipitation, translate to smaller increases in glacier runoff (+3% and +7% decade −1 ) and total watershed runoff (+1.4% and +3% decade −1 ). These results suggest that the western Juneau Icefield watersheds are still in an increasing glacier runoff period prior to reaching "peak water." In terms of timing, we find that maximum glacier ice melt is occurring earlier (2.5 days decade −1 ), indicating a change in the source and quality of freshwater being delivered downstream in the early summer. Our findings highlight that even in maritime climates with large precipitation variability, high latitude coastal watersheds are experiencing hydrological regime change driven by ongoing glacier mass loss. Plain Language Summary: Compared to freshwater from rain or melted snow, meltwater from glaciers is physically and chemically unique, and serves an important role in high latitude coastal hydrology and ecology. Today, as glaciers worldwide are shrinking, the amount and timing of glacier meltwater delivery into streams are both changing, with potential impacts for infrastructure and ecosystems. However, those changes may be difficult to identify in coastal areas due to large differences in year‐to‐year precipitation. Here, we use computer modeling to examine freshwater changes for the western Juneau Icefield in Southeast Alaska between 1980 and 2016. We detect several changes, including increases in the amount of glacier meltwater occurring annually and in spring (+10% and +16% per decade), and in total basin freshwater (+1.4% and +3% per decade). This suggests the area is still in a period of increasing glacier meltwater before the glaciers shrink to the extent that the amount diminishes. We also find that the peak amount of glacier meltwater is occurring earlier (2.5 days per decade), meaning that the type of freshwater arriving downstream at that time of year is changing. Our findings highlight that high latitude coastal watersheds are experiencing observable changes in freshwater as glaciers continue to shrink. Key Points: Discharge from western drainages of Juneau Icefield is increasing and has yet to pass "peak water" as glaciers lose mass Annual glacier ice melt volumes have increased by 10% per decade, glacier runoff by 3%, and total runoff by 1.4% Peak glacier ice melt volumes are increasing and arriving earlier, with impacts for downstream ecosystem function